(untitled) (Iranian Journal of Kidney Diseases, 2025)
Introduction. Uremic pruritus (UP) is a disturbing symptom in a quite large proportion of hemodialysis (HD) patients. Recent studies have indicated a potential role of interleukin-31 (IL-31) in the pathophysiology of pruritus, and it is becoming a promising therapeutic target for UP. Hemoperfusion (HP) is an extracorporeal technique that has been shown to be effective in absorbing molecules which may be responsible for inducing pruritus. In this study, we conducted this study to explore whether additional HP could enhance the removal of IL-31 in UP patients. Methods. The study was conducted in two parts. In Part A, the prevalence and intensity of UP were recorded and the basal serum IL-31 level was determined three times a week in HD patients. Patients with detectable serum IL-31 levels in part A were included in Part B. Each patient had two 4-h test sessions: conventional HD or HD plus HP (HDHP). The reduction ratio (RR) of IL-31 from HD and HDHP was compared. Results. Forty patients completed part A and 40% of them were suffering from UP. Serum IL-31 was detected at significantly higher percentages in UP patients than in non-UP patients (50% vs 4.2%). Serum levels of IL-31 in UP patients were significantly higher than that in non-UP patients (median: 8.35pg/ml vs 7.8pg/ml). Serum IL-31 levels were significantly correlated with pruritus intensity in patients with UP(r = 0.55, P < .05). Eight patients were enrolled and completed part B. The use of combined HD and HP treatment produced a better RR for IL-31 than HD alone (34.26 ± 1.43% vs 15.28 ± 2.11%, P < .01). Conclusions. IL-31 may play an important role in the pathophysiology of uremic pruritus. The addition of hemoperfusion to conventional hemodialysis provides enhanced removal of IL-31.